Memahami Perilaku Dan Ruang Digital Dalam Perspektif Psikologi - Muntaha Nour; Samsul Bahri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Online behavior in today's digital era is a phenomenon that cannot be ignored. With the development of information and communication technology, individuals engage in complex interactions in the digital space. This article aims to understand online behavior and digital space through the lens of cyber psychology. Through a descriptive qualitative approach and literature study, this research examines the factors that influence online behavior, its impact on individuals, and the relationship between behavior, digital space, and cyber psychology. The results show that online behavior is influenced by various psychological and social factors, and digital space has a significant impact on individuals' identity and mental health.